Product Quality and Innovation as Drivers of Chocodot Competitive Advantage - Athoillah, Fikri Aziz (Entrepreneurship Faculty, Universitas Garut, 2025)
This study aims to examine the effect of product innovation and product quality on competitive advantage in Chocodot products. A quantitative research design with a descriptive approach was employed, involving 123 respondents selected through simple random sampling. Data were collected using a questionnaire and analyzed with SPSS 27 through multiple linear regression, data quality tests, coefficient of determination, and hypothesis testing. The findings indicate that product innovation influences competitive advantage by 67.1%, product quality contributes 70.2%, and both variables simultaneously account for 74.8%, while 25.2% is explained by other factors beyond this research. These results highlight that product innovation and product quality are critical determinants of competitive advantage, providing a strategic foundation for the development of local SMEs.